Structural empowerment to ease the transition of new nurse graduates : exploring the experiences of operational managers in primary healthcare clinics - Nzimande, Londiwe (Stellenbosch : Stellenbosch University, 2024)
Thesis (MNur)--Stellenbosch University, 2024.